2009
DOI: 10.1007/s11524-009-9376-1
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support using a Mobile Access Van Promotes Safety and Harm Reduction Strategies among Sex Trade Workers in Vancouver’s Downtown Eastside

Abstract: Women in the sex trade whose economic and social base are urban streets face multiple dangers of predation, isolation, and illness. A Mobile Access Project (MAP) to provide emergency medical help, peer counseling, condoms and clean needles, resource information and referral, and a place of respite and safety was initiated for sex trade workers in Vancouver, British Columbia, Canada. We conducted surveys with 100 women sex workers who accessed MAP services and reviewed MAP logbooks to document use of services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Salmon et al (2009) reported that 79.2% of the women in their study group had recently experienced violence, and two of the women were killed in violent circumstances during the course of the study-thereby illustrating the profound cruelty to which this population is exposed. In the downtown eastside of Vancouver, over 60 sex trade workers have gone missing since 1980 (Janssen et al, 2009). Salmon et al (2009) also emphasize that women experience violence-not only from their peers, drug dealers, interpersonal relationships, and clients in the sex trade-but also from the health care system, and from the health care providers.…”
Section: Health Care Needs and Risksmentioning
confidence: 99%
See 4 more Smart Citations
“…Salmon et al (2009) reported that 79.2% of the women in their study group had recently experienced violence, and two of the women were killed in violent circumstances during the course of the study-thereby illustrating the profound cruelty to which this population is exposed. In the downtown eastside of Vancouver, over 60 sex trade workers have gone missing since 1980 (Janssen et al, 2009). Salmon et al (2009) also emphasize that women experience violence-not only from their peers, drug dealers, interpersonal relationships, and clients in the sex trade-but also from the health care system, and from the health care providers.…”
Section: Health Care Needs and Risksmentioning
confidence: 99%
“…Although the focus of this paper is on marginalized adult women in general, it is important to note that in this literature review there is an over representation of marginalized Aboriginal women (Butters & Erickson, 2003 ;Deering et al, 2011a;Janssen et al , 2009;Kurtz et al, 2008;Lazarus et al, 2012;Marshall, Charles, Hare, Ponzetti, & Stokl, 2005;Salmon et al , 2009). For example, Marshall et al (2005) found that, of the women using Sheway, the downtown eastside street-front service, 80.7% were Aboriginal.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%
See 3 more Smart Citations